ЯКІСТЬ ВОДИ ЯК ІНДИКАТОР СТАЛОГО РОЗВИТКУ. - Скиба, Вікторія Павлівна; Skyba, Viktoriia; Вознюк, Н. М. (My University, 2024)
Water pollution remains a significant issue in the modern world, and its resolution has become a top priority for sustainable development. The 2030 Agenda for Sustainable Development prioritizes water quality in international actions by establishing a specific goal (SDG 6: "Ensure availability and sustainable management of water and sanitation for all"), aimed at addressing the urgent challenges related to water pollution.
Keywords: цілі сталого розвитку; sustainable development goals; ЦСР; SDG